Sinkage and Trim of Modern Container Ships in Shallow Water - Gourlay, Tim; Hun Ha, J.; Mucha, P.; Uliczka, K. (Research Gate, 2015)
This paper concerns dynamic sinkage and trim of modern container ships. A review is made of changing container ship hull designs up to the present time, together with available model test data for sinkage and trim. Two potential flow methods (slender-body method and Rankine-source method) are discussed with reference to the model test results. It is shown that slender-body theory is able to give good predictions of dynamic sinkage and trim in wide canals or open water, while Rankine-source methods offer an accurate solution particularly for ships at high speed in narrow canals.